CONDUCTIVITY TO RUST IN COFFEE UNDER DIFFERENT WOODEN AND FRUIT TREE INTERCROPPING SYSTEMS - Chalfoun, Sara Maria; de Pádua Martins, Carla; Sousa Machado Matos, Christiano; Botelho Pereira, Alessandro; Silva, Vicentina Nazaré (Coffee Science - ISSN 1984-3909, 2018)
The coffee intercropping with fruit and wooden species of economic value has been presented as a viable alternative for coffee cultivation in order to mitigate adverse environmental conditions for coffee trees, among other factors. Adapting the crop management to the new conditions stablished by the system is fundamental to obtain success on intercropping. One of the most serious diseases for the crop is the rust caused by Hemileia vastatrix., which may have its severity increased in function of the microclimate conditions provided by the trees. In this sense, the disease behavior under different intercropping systems and consequent different need to adapt the control measures when compared to the cultivation in full sun should be investigated. The present study was conducted aimed to verify the impact of tree systems composed by three wooden species, Cedar (Acrocarpos fraxinifolius), African mahogany (Khaya ivorensis ), Teak (Tectona grandis ) and two species of fruit trees, avocado (Persea Americana) and macadamia (Macadamia integrifolia) planted in different spacing over the occurrence and evolution of rust.It was possible to observe that coffee rust began to progress in the coffee plants from the month of February reaching a peak in September in all the treatments. Differences were observed in the progress curves of the disease, especially in the species that presented larger canopy such as avocado. Further studies are suggested with the purpose of establishing the microclimatic changes provided by the cultivation of different wooden and fruit species in intercropping with coffee, according to the dynamics of the climate and their development.